2003
DOI: 10.1080/07315724.2003.10719276
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of the Effect of Bifidobacteria-Fermented Milk on Ulcerative Colitis

Abstract: Supplementation with the BFM product was successful in maintaining remission and had possible preventive effects on the relapse of ulcerative colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
188
1
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(199 citation statements)
references
References 22 publications
3
188
1
7
Order By: Relevance
“…ishikawa et al (ref. 30 ) reported that Bifidobacteria-fermented milk (BFm) supplementation reduces the luminal butyrate concentration, a key molecule in the remission of colitis. This reduction reflects the increased uptake or oxidation of scFas by the improved colorectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…ishikawa et al (ref. 30 ) reported that Bifidobacteria-fermented milk (BFm) supplementation reduces the luminal butyrate concentration, a key molecule in the remission of colitis. This reduction reflects the increased uptake or oxidation of scFas by the improved colorectal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…El estudio de Ishikawa y colaboradores en Japón mostró el éxito de esta conducta en el mantenimiento de la remisión, con una reducción significativa de las exacerbaciones, y posibles efectos preventivos en recaídas con el uso de un suplemento de leche fermentada con bifidobacteria (simbiótico) 100 mL/día durante 1 año en 41 pacientes. Hallazgo reafirmado en un nuevo estudio realizado por el mismo autor en 2011, con evidencia de mejoría clínica, colonoscópica y disminución de niveles de mieloperoxidasa en 21 pacientes (p <0,05) (42,43). En el mismo país, el estudio de Fujimori con 31 pacientes comparó Bifidobacterium longum 2 x 10 9 UFC y 8 g de psyllium (prebiótico) con simbiótico únicamente y encontró mayor impacto con manejo combinado, con remisión mantenida durante las 4 semanas de tratamiento (p=0,03) (44).…”
Section: Colitis Ulcerativaunclassified
“…A recent clinical trial demonstrated that treatment of patients with Bfdbm fermented milk compared to placebo leads to a significant decrease in a clinical activity index score, as well as a significant decrease in endoscopic and histological scores after 12 weeks of treatment [78].…”
Section: Probiotics To Treat Active Ucmentioning
confidence: 99%